2005
DOI: 10.1577/1548-8446(2005)30[11:hriws]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hatchery Reform in Washington State

Abstract: Hatcheries support nearly all major fisheries for Pacific salmon (Oncorhynchus spp.) and steel‐head (anadromous O. mykiss) in the Pacific Northwest. However, hatcheries have been a major source of controversy for over 30 years. The Hatchery Scientific Review Group (HSRG) was tasked by Congress to identify solutions to well‐known problems so hatcheries could better meet their goals of supporting sustainable fisheries and assisting with the conservation of natural populations. We reviewed over 100 facilities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…The amount of straying that a wild population can tolerate is uncertain. The guiding management plan for hatcheries in PWS suggests an upper limit of hatchery strays of 2% (PWS CRRPT 1994), while other studies suggest that thresholds as high as 5% or 10% may be detrimental to wild salmon populations through mechanisms discussed above (Ford 2002;Mobrand et al 2005). In our study, we found a wide range of straying proportions across years, but hatchery pink, chum, and sockeye salmon exceeded all proposed thresholds of straying into many wild salmon spawning locations.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The amount of straying that a wild population can tolerate is uncertain. The guiding management plan for hatcheries in PWS suggests an upper limit of hatchery strays of 2% (PWS CRRPT 1994), while other studies suggest that thresholds as high as 5% or 10% may be detrimental to wild salmon populations through mechanisms discussed above (Ford 2002;Mobrand et al 2005). In our study, we found a wide range of straying proportions across years, but hatchery pink, chum, and sockeye salmon exceeded all proposed thresholds of straying into many wild salmon spawning locations.…”
Section: Discussionmentioning
confidence: 47%
“…The straying of hatcheryreared salmon, on the other hand, may be disruptive to wild populations. A few generations of artificial breeding and rearing of salmon in a protected environment can lead to domestication, altered gene frequencies, and phenotypic changes that reduce the adaptive fitness of hatchery salmon (Fleming and Gross 1993;Berejikian et al 2001;Myers et al 2004;Mobrand et al 2005;Araki et al 2007;Naish et al 2007;Araki et al 2008;Grant 2012). Hence, hybridizations between hatchery and wild fish may also decrease the adaptive fitness of wild populations (McClelland et al 2005;Ford et al 2006;Wessel et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about how supplementation may change the genetic composition of salmonid populations prompted Mobrand et al (2005) to propose that the proportion of natural-origin fish on spawning grounds and in hatchery broodstocks should always be greater than the corresponding proportion of hatchery fish. This protocol dilutes potential domestication because fifty percent or more of the genes transmitted from one generation to the next by hatchery fish are subjected to natural selection pressures (Mobrand et al 2005).…”
mentioning
confidence: 99%
“…Skagit Bay (northern) and Nisqually Reach (southern) are two of the most biologically different areas but are among the least urbanized estuaries in Puget Sound. However, human activity may play a role in several interacting ways: (1) locally, such as through nutrient loading, shoreline (Shipman et al 2010) and substrate hardening, and manipulation of the pelagic fish fauna by hatchery supplementation (Mobrand et al 2005) and fishery harvests (sport, commercial, and subsistence); and (2) globally, such as through species introductions (Cohen 1998;Mills et al 2000;Cohen et al 2001) or influences on climate that affect physical forcing and nutrient delivery from the Pacific Ocean or surrounding watersheds (Snover et al 2005;Moore et al 2008). Efforts to understand the myriad effects of human activity and their interactions on the pelagic ecosystem in Puget Sound have been negligible.…”
Section: Discussionmentioning
confidence: 99%